PRAKTIK REKRUITMEN DAN SELEKSI: STUDI KASUS MITRA SENSUS BADAN PUSAT STATISTIK - Juliansyah Noor; Eben Baenuri; Soleh Soleh; Ade Jaya Sutisna (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2020)
This study aims to detail the recruitment and selection practices of census partner Statistics Indonesia located in Banten. This qualitative study uses snowball sampling to provide data on census partner recruitment and selection. The interviews organize in Banten's are noted. The interviews are coded to identify similarities and dissimilar themes. This study identifies internal and external census partner recruitment, as the predominant census partner recruitment and selection practices. The study identifies successful recruitment and selection practices adopted by Statistics Indonesia. As state institutions significantly increase their presence in Banten.